Effects of early-life competition and maternal nutrition on telomere lengths in wild meerkats. Issue 1861 (30th August 2017) - Cram, Dominic L.; Monaghan, Pat; Gillespie, Robert; Clutton-Brock, Tim
Abstract : Early-life adversity can affect health, survival and fitness later in life, and recent evidence suggests that telomere attrition may link early conditions with their delayed consequences. Here, we investigate the link between early-life competition and telomere length in wild meerkats. Our results show that, when multiple females breed concurrently, increases in the number of pups in the group are associated with shorter telomeres in pups. Given that pups from different litters compete for access to milk, we tested whether this effect is due to nutritional constraints on maternal milk production, by experimentally supplementing females' diets during gestation and lactation. While control pups facing high competition had shorter telomeres, the negative effects of pup number on telomere lengths were absent when maternal nutrition was experimentally improved. Shortened pup telomeres were associated with reduced survival to adulthood, suggesting that early-life competition for nutrition has detrimental fitness consequences that are reflected in telomere lengths. Dominant females commonly kill pups born to subordinates, thereby reducing competition and increasing growth rates of their own pups. Our work suggests that an additional benefit of infanticide may be that it also reduces telomere shortening caused by competition for resources, with associated benefits for offspring ageing profiles and longevity.